Admission to Accounting Programs: Using a Discriminant Model as a Classification Procedure - Clark, Ronald L.; Sweeney, Robert B. (The Accounting Review, 1985)
[This paper uses discriminant analysis as a foundation for an admissions policy for accounting majors. The discriminant model is capable of correctly classifying students into Accept/Reject groups with a statistical accuracy of 78 percent using only three characteristics-grade-point average at 45 semester hours, grade in college mathematics, and grade in English composition. The model, more importantly, correctly classifies 90 percent of those students who, according to the model's criterion, should be rejected. Alternatively, the model is capable of identifying the same percent of those students who perform exceedingly well in accounting. This technique, together with a review and appeal procedure, provides a method of restricting enrollment while still meeting today's demand for quality accounting students.]